FAKTOR-FAKTOR YANG MEMPENGARUHI FINANCIAL PERFORMANCE PADA PERUSAHAAN MANUFAKTUR TAHUN 2015-2018 - Joshua, Vidyarto Nugroho (Fakultas Ekonomi, Universitas Tarumanagara, 2020)
The purpose of this study was to show how the influence of corporate social responsibility, institutional ownership and board size on financial performance. The subjects in this study were 66 samples of manufacturing companies listed on the Indonesia Stock Exchange (IDX) in 2015 to 2018. The sample selection in this study was carried out using a sample selection method based on criteria. The data in this study were processed with the Eviews program version 9. The results of this study indicate that the variables of corporate social responsibility and institutional ownership do not have a significant effect on financial performance. Meanwhile, the variable board size has a significant influence on financial performance.